2019
DOI: 10.1111/bph.14757
|View full text |Cite
|
Sign up to set email alerts
|

The plant product quinic acid activates Ca2+‐dependent mitochondrial function and promotes insulin secretion from pancreatic beta cells

Abstract: Background and Purpose Quinic acid (QA) is an abundant natural compound from plant sources which may improve metabolic health. However, little attention has been paid to its effects on pancreatic beta‐cell functions, which contribute to the control of metabolic health by lowering blood glucose. Strategies targeting beta‐cell signal transduction are a new approach for diabetes treatment. This study investigated the efficacy of QA to stimulate beta‐cell function by targeting the basic molecular machinery of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…In the present study, feeding with cranberry or wild blueberry pomaces significantly increased the QA level in the plasma of chickens. Thus, feed supplementation with cranberry and blueberry products could reduce oxidative stresses and improved metabolic functions against reactive oxygen species damage in chickens due to synergistic effects of multiple-phytochemical combinations of both berries ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, feeding with cranberry or wild blueberry pomaces significantly increased the QA level in the plasma of chickens. Thus, feed supplementation with cranberry and blueberry products could reduce oxidative stresses and improved metabolic functions against reactive oxygen species damage in chickens due to synergistic effects of multiple-phytochemical combinations of both berries ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the impacts of Ca 2+ homeostasis [11,12] and mitochondrial function [13] on β-cell function are widely accepted, and despite the unquestionable role of mitochondrial Ca 2+ for pancreatic β-cell signal transduction [5][6][7], very few therapies or interventions based on the modulation of mitochondrial Ca 2+ have been developed until now. In this context, we recently demonstrated that natural bioactive quinic acid increases glucose-stimulated mitochondrial Ca 2+ rise, enhancing insulin secretion in both INS-1E β-cells and mouse islets, and improves glucose tolerance in mice [14]. In that study, quinic acid was not a direct activator of MCU but it enhanced the release of Ca 2+ from the endoplasmic reticulum, improving Ca 2+ transmission between the endoplasmic reticulum and mitochondria.…”
Section: Introductionmentioning
confidence: 90%
“…Pereira et al, 26 in a screening study on thirty-nine quinoa genotypes, also reported the presence of oxalic acid and, similarly, traces of fumaric acid; however, they did not detect quinic and malic acids. In a recent study performed by Heikkilä et al 32 in an in vivo mice model, it was suggested that quinic acid could be helpful in the treatment of diabetes, by promoting insulin secretion from pancreatic beta cells.…”
Section: Nutritional Value and Physicochemical Compositionmentioning
confidence: 99%